THU0406 Histological Findings of Spleen Affected by Adult Onset Still's Disease: an Analysis of 3 Cases. (10th June 2014) - Sakairi, T.; Okabe, S.; Ohishi, Y.; Sakurai, N.; Ikeuchi, H.; Kaneko, Y.; Maeshima, A.; Hiromura, K.; Nojima, Y.
Abstract : Background: Diagnosis of adult onset Still's disease (AOSD) is based on sets of several clinical and laboratory criteria, because no specific test is available. The differential diagnosis includes malignant lymphoma and infection. A recent case-series study using positron emission tomography/computed tomography (PET/CT) have shown that injected 18F-fluoro-deoxyglucose (FDG) accumulates in spleens of AOSD patients with high frequency up to 90.9%, along with bone marrow (100%) [1]. It is currently unknown which cell types contribute to the FDG retention in spleens of AOSD patients, while granulocytic hyperplasia in bone marrow reported as a common feature of AOSD may be responsible for the FDG uptake by bone marrow [2]. Objectives: We aimed to present AOSD cases that underwent spleen biopsies to rule out malignant lymphoma. Methods: Three AOSD patients (aged 31, 40 and 48 years) with high FDG accumulation in spleens and bone marrow (mean max SUV, 5.46 and 4.70, respectively) were subjected to percutaneous spleen and bone marrow biopsies, and specimens were histologically analyzed. The diagnosis of AOSD was made according to Yamaguchi criteria. Results: Severe infiltration of neutrophils into red pulps was observed in all spleen biopsies (shown in image), which resembled acute splenitis caused by sepsis [3]. Plasmacytic hyperplasia was found in 1 among the 3 biopsies. In addition, we identified mild eosinophilic infiltration in each biopsy. Bone marrow examination revealed hypercellular bone marrow with granulocytic hyperplasia and histiocytic hemophagocytosis in 1, and normocellular bone marrow with normal myeloid/erythroid ratio in 2 among the 3 biopsies, which is inconsistent to the previous report [2]. Conclusions: Our results indicate that neutrophils infiltrating in red pulps are relevant to the FDG-uptake by spleens among AOSD patients. Spleen biopsies are useful to differentiate AOSD from malignant lymphoma, but unable to exclude sepsis. References: Yamashita, H., et al., Clinical value of F-fluoro-dexoxyglucose positron emission tomography/computed tomography in patients with adult-onset Still's disease: A seven-case series and review of the literature. Mod Rheumatol, 2013. [Epub ahead of print] Min, J.K., et al., Bone marrow findings in patients with adult Still's disease. Scand J Rheumatol, 2003. 32(2): p. 119-21. Feig, J.A. and S.J. Cina, Evaluation of characteristics associated with acute splenitis (septic spleen) as markers of systemic infection. Arch Pathol Lab Med, 2001. 125(7): p. 888-91. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.1443